Pregunta
Simplify. \[ \frac{y}{y^{-3}} \] Write your answer with a positive exponent only. G
Ask by Haynes Black. in the United States
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
\( y^4 \)
Solución
To simplify the expression \(\frac{y}{y^{-3}}\) and ensure all exponents are positive, follow these steps:
1. **Use the Law of Exponents**:
The law of exponents states that \(\frac{y^a}{y^b} = y^{a - b}\).
Applying this to your expression:
\[
\frac{y}{y^{-3}} = y^{1 - (-3)} = y^{1 + 3} = y^4
\]
2. **Alternative Method - Multiplying by the Reciprocal**:
Alternatively, you can rewrite the division as multiplication by the reciprocal:
\[
\frac{y}{y^{-3}} = y \times y^{3} = y^{1 + 3} = y^4
\]
Both methods lead to the same result.
**Final Answer:**
\[
y^4
\]
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Mind Expander
To simplify \(\frac{y}{y^{-3}}\), we can use the property of exponents that states \(\frac{a^m}{a^n} = a^{m-n}\). In this case, we have: \[ \frac{y^1}{y^{-3}} = y^{1 - (-3)} = y^{1 + 3} = y^4. \] So, the simplified expression is \(y^4\).
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium